2005
DOI: 10.1097/01.inf.0000148923.46453.48
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Reactogenicity of Four Doses of Diphtheria-Tetanus-Three-Component Acellular Pertussis-Hepatitis B-Inactivated Polio Virus-Haemophilus influenzae Type b Vaccine Coadministered with 7-Valent Pneumococcal Conjugate Vaccine

Abstract: Coadministration of the DTPa-HBV-IPV/Hib and 7vPn vaccines at separate injection sites during the same vaccination visit was effective and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 17 publications
5
32
0
8
Order By: Relevance
“…We found no association between anti-HBs levels <10 mIU/ml and concomitant vaccination with MMR or pneumococcal vaccine ; however, the number of concomitantly vaccinated children was small. Previous studies have reported lower geometric mean anti-HBs levels with concomitant administration of hexavalent vaccines and pneumococcal conjugate vaccine [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…We found no association between anti-HBs levels <10 mIU/ml and concomitant vaccination with MMR or pneumococcal vaccine ; however, the number of concomitantly vaccinated children was small. Previous studies have reported lower geometric mean anti-HBs levels with concomitant administration of hexavalent vaccines and pneumococcal conjugate vaccine [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…La administración de esta vacuna junto con otras del calendario infantil no conlleva aumentos relevantes en la frecuencia de las reacciones adversas respecto a las que pueden atribuirse a cada vacuna por separado [49][50][51][52][53] .…”
Section: Seguridadunclassified
“…Los ensayos que probaron pautas de 3 ó 4 dosis lograron respuestas inmunes por encima de 0,35 g/ml frente a todos los serotipos vacunales entre el 82% y el 100% de los niños vacunados [49][50][51][52] . Cuando la VNC7v se administra junto con otras del calendario infantil, los títulos de anticuerpos que se alcanzan frente a algunos antí-genos son ligeramente inferiores que cuando se administra aisladamente, pero esta diferencia parece no tener relevancia clíni-ca [49][50][51]53 . La VNC7v ha demostrado ser capaz de inducir la producción de anticuerpos incluso en niños con infecciones recurren-tes que no respondían a la vacuna polisacárida 56 .…”
Section: Inmunogenicidadunclassified
“…13 Only two published studies evaluate the immune response following simultaneous vaccinations with Infanrix hexa (DTaP-IPV-HBV/HIB; GlaxoSmithKline) and Prevenar (7-valent pneumococcal vaccine). [14][15][16] In one study, the seroconversion rates of both HBV and Hib were substantially (but not significantly) lower at 1 month after the booster vaccination in the study group (each 96.8%) than in the control group (each 99.1%; Table 1). 14 In both studies, the geometric mean concentration (GMC) of HBV antibodies was reduced, but again, not significantly ( Table 1).…”
Section: Prevenar Given Simultaneously With Hexavalent Vaccines To Chmentioning
confidence: 99%
“…[14][15][16] In one study, the seroconversion rates of both HBV and Hib were substantially (but not significantly) lower at 1 month after the booster vaccination in the study group (each 96.8%) than in the control group (each 99.1%; Table 1). 14 In both studies, the geometric mean concentration (GMC) of HBV antibodies was reduced, but again, not significantly ( Table 1). The two-sided 95% confidence interval (CI) included the 95% seroconversion cut-off level (>10 IU/l) in both studies, the minimum to be reached in universal programmes for children.…”
Section: Prevenar Given Simultaneously With Hexavalent Vaccines To Chmentioning
confidence: 99%